Talking about God : the concept of analogy and the problem of religious language - White, Roger M. (Transcending boundaries in philosophy and theology., 2010)
A fundamental question for theology is the question how we are to understand the claims that we make about God. The only language we can understand is the language we use to talk about human beings and their environment. How can we use that language to talk about God while respecting the infinite difference between God and humanity?The traditional answer has been to appeal to the concept of analogy. However, that appeal has been interpreted in widely different ways. This book aims to clarify the question and this answer by an analysis of the concept. It begins with an exploration of the way th.